BUFFER ZONE BANDARA KERTAJATI DALAM MENGEMBANGKAN DESTINASI PARIWISATA DI SUMEDANG - Gunawan, Agung Arif (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2022)
In developing tourist, with the construction of Kertajati Airport and the access to Cisumdawu toll road, that can improve the economy of the local and the standard of living and the economy of the local community. Sumedang has been planned to become a buffer zone of Kertajati Airport area that can support tourism and economic activities. With the plan to open toll exit access in 5 districts in Sumedang,, the local government plans to develop tourism destinations in the sub-district to be developed into priority destinations. The five tourist destinations include: Pangjugjuga (Pamulihan), Geusan Ulun Museum (North Sumedang), Tampomas Green Park (Cimalaka), Cipanas Sekarwangi (Conggeang) and Panenjoan (Ujungjaya). This study aims to determine the condition of tourist destinations in the development buffer zone area in Sumedang. The operational variables of the buffer zone and the transit destination variables used provide an overview of the phenomena that occur in each tourist destination. The type of research used is qualitative with descriptive method. Data collection techniques used are triangulation data collection techniques; field observation, deep interview and literature study, while the data analysis used was the point rating scale model data analysis. From the results of data processing, it is found that there needs to be a policy from the government, both in the form of standard and centralized regulations or regulations regarding the management of tourist destination areas (tourism human resource development, ecosystem conservation) and increasing the participation of local communities/communities and regional tourism actors in activities tourism in the Sumedang